2006
DOI: 10.1152/ajprenal.00357.2005
|View full text |Cite
|
Sign up to set email alerts
|

SMP-534 ameliorates progression of glomerular fibrosis and urinary albumin in diabeticdb/dbmice

Abstract: benzamide (SMP-534) reduces extracellular matrix (ECM) production induced by transforming growth factor-␤ (TGF-␤) in vitro and prevents the accumulation of ECM in glomeruli in rat Thy-1 nephritis models. In this study, we examined the longterm effects of SMP-534 on renal insufficiency and glomerulosclerosis in db/db mice, which are models of type 2 diabetes. A diet containing SMP-534 was given to the mice from the age of 9 to 25 wk, and blood and urine analysis were performed at 8, 17, and 25 wk. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
3
26
1
Order By: Relevance
“…Similarly, the Ccr data were inconclusive, although these levels in uninephrectomized db/db or db/m mice were significantly higher than those in db/m mice without uninephrectomy. These results are consistent with reports by other groups 35,36 and may still reflect hyperfiltration, an early symptom of diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, the Ccr data were inconclusive, although these levels in uninephrectomized db/db or db/m mice were significantly higher than those in db/m mice without uninephrectomy. These results are consistent with reports by other groups 35,36 and may still reflect hyperfiltration, an early symptom of diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 93%
“…The Ccr levels of db/db mice are usually higher than those of db/m mice. 35 With uninephrectomy, the Ccr levels in either db/m or db/db mice are significantly increased as compared with those of db/m mice with two kidneys. 35 After 20 wk of sustained hyperglycemia and renal hyperfiltration, kidneys from untreated unine- Figure 5.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, we have studied whether SMP-534 has beneficial effects on renal fibrosis. We have shown that treatment with SMP-534 inhibits accumulation of ECM in kidney of diabetic db/db mouse or 5/6 nephrectomized rats and ameliorates renal function (13,15). In the present study, we investigated whether SMP-534 has beneficial effects on pulmonary fibrosis in bleomycin-treated hamsters.…”
mentioning
confidence: 89%
“…Several AGE inhibitors also decrease TGF-levels. (Turgut F,2010, Sugaru E., 2006) CTGF Inhibitors -Connective tissue growth factor (CTGF/CCN2) has been associated with fibrosis in various tissues including the kidney. It is up-regulated in most models of DN.…”
Section: Antifibrotic Agents and Growth Factor Inhibitorsmentioning
confidence: 99%